Pengaruh Penerapan Metode Ripping pada Penambangan Batubara Terhadap Produktivitas Crushing Plant (Studi Kasus: PT Mifa Bersaudara, Aceh Barat) - Haqul Baramsyah; T. Zulfikar; Nurul Kamal; Melya Gusnira Nilda (Jurnal Teknik Mesin Unsyiah, 2020)
PT Mifa Bersaudara is a coal mining company that operates in Meulaboh, Aceh Barat. The main activities are extracting coal from the ground, loading, hauling, and crushing the coal to a specific size. There are two crushing plants that currently running at the site, Fix Crusher 01 (FC01) and Fix Crusher 02 (FC02). The production target for these crushers are 550 tons/hours and 450 tons/hours, respectively. However, the crushers could not meet the target. The main problem is the number of boulder materials from mining front almost 8.22 %, exceeding the optimum percentage of crusher’s input. In order to fix this matter, the application of ripping method in mining the coal is needed. This method utilizes Bulldozer CAT D8R, equipped with ripper, to break down the coal seam. Based on the calculation, this method could decrease the percentage of boulder materials from 8.22% to 3.04%. It enhances the productivity of excavator from 229.71 tons/hours to 284.05 tons/hours. Then, the productivity of the crushers also increase from 545 to 552 tons/hours for FC01 and from 347 to 452 tons/hours for FC02. Therefore, the application of ripping method in excavating the coal seam could increase the productivity of coal crushing plant.